Pengaruh Pendidikan Dan Pelatihan Terhadap Efektivitas Pelaksanaan Pelayanan Administrasi Kepegawaian di BKDD Kabupaten Kepulauan Talaud - wando, nova (JURNAL ADMINISTRASI PUBLIK, 2013)
Abstract : Education and training is a very important factor to improve / develop the knowledge , skills and attitudes of civil servants so that it can carry out its duties effectively . This study is intended to answer the question of whether there is an influence on the effectiveness of education and training in administrative services kepagawaian BKDD Talaud Islands . Methods of research using quantitative methods . Sources of data / research respondents were all civil servants on BKDD Talaud Islands by 35 people . Collecting data using questionnaires and assisted with interviewing techniques . Analysis is a statistical analysis used linear regression and product moment correlation .Statistical analysis showed : ( 1 ) Education and training has a positive and significant functional relationship on the effectiveness of administrative services kepagawaian ( 2 ) education and training have degrees of correlation and determination were high and significant impact on the effectiveness of personnel administration services .Based on the results of the study concluded that education and training positive and significant impact on the effectiveness of personnel administration services in BKDD Talaud Islands . Based on the conclusion of the study suggested that the education and training needs to be improved to employees in BKDD Talaud Islands , especially functional education and technical training , because training is related directly to the enhancement of knowledge and skills to perform job duties of the employee .Keywords : Education and Training , Administrative Services Officer Effectiveness